Comparison of simultaneous and sequential administration of fentanyl–propofol for surgical abortion: a randomized single-blinded controlled trial. (4th July 2017) - Gao, Wei; Sha, Baoyong; Zhao, Yuan; Fan, Zhe; Liu, Lin; Shen, Xin
Abstract: Propofol lipid emulsion (PLE) is a nanosized sedative, and it is used with a combination of salted antalgic prodrug, fentanyl citrate (FC). To illustrate the synergistic effect of mixing, we compared the sedation/analgesia resulting from simultaneous and sequential administration in surgically induced abortion (No. ChiCTR-IPC-15006153). Simultaneous group showed lower bispectral index, blood pressure, and heart rate, when cannula was inserted into the uterus. It also showed less frequency of hypertension, sinus tachycardia, movement, pain at the injection site, and additional FC. Therefore, premixing of PLE and FC enhanced the sedation and analgesia; stabilized the hemodynamics; lessened the incidence of movement and injection pain; and reduced the requirement of drugs.